CONFLICTOGENIC POTENTIAL OF ETHNOPOLITICAL PROCESSES IN THE NORTH AND SOUTH CAUCASUS: GENERAL AND SPECIAL - A. M. Erokhin; S. M. Vorobev; E. A. Avdeev (Современная наука и инновации, 2022)
The relevance of the topic is due to the presence of conflicting opportunities for ethnopolitical and logical processes in the Caucasus, which is also a high level of social and political activity of youth characteristic of the region and its active participation in socio-political processes. Materials and methods, results and discussions The article defines the attitude of young people to ethno-political processes in the Caucasus macro-region, presents an analysis of assessments and ideas of young people about the causes of ethno-political conflicts, the degree of conflict of ethno-political processes, the presence / absence of communication problems, the interaction of people of different nationalities, religions and identifies the causes of ethno-political contradictions and disagreements in the region. The basic research is the sociological method, the method ofpolitical analysis and the use of statistical data. The source base was the results of a sociological survey of undergraduate and graduate students at the age of 18-24 from universities in the North and South Caucasus, conducted as part of the project "Ethnopolitical Processes in the Caucasus in the Assessments and Representations of Modern Youth".